Strategi Pengembangan Agribisnis Kopi di Kabupaten Bangka Tengah Provinsi Kepulauan Bangka Belitung - Novandri, Ogi; karsiningsih, Eni; Astuti, Rufti Puji (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
This study aims to formulate coffee agribusiness development strategies in Central Bangka Regency and formulate priority strategies for coffee agribusiness development strategies in Central Bangka Regency. This research was conducted from November to January 2024 in Central Bangka Regency. The research method used in this research is survey. The sampling method used was purposive sampling with a sample of 30 respondents. The analysis method used descriptive qualitative and Strengths, Weakness, Opportunities, and Threats (SWOT) analysis and Quantitative Strategic Planning Matrix (QSPM). The results showed that the overall internal factor value was 2.57 and the external factor value was 2.77. Three alternative strategies that are appropriate to be selected as the main strategy are the development of coffee agribusiness systems based on local resources and culture, utilization of environmentally friendly technology and market orientation with a TAS value of 6.31 (Rank I). Development of coffee-based integrated agribusiness in each major coffee-producing region with a TAS value of 6.09 (Rank II). Development of coffee agribusiness systems directed at increasing competitiveness through fostering improvements in the quality and appearance of coffee and processed products with a TAS value of 6.01 (Rank III).